2020
DOI: 10.1186/s40795-020-00347-6
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal study of fruit juice consumption during preschool years and subsequent diet quality and BMI

Abstract: Background The role of fruit juice in pediatric dietary guidelines continues to be controversial, particularly with respect to concerns about unhealthy dietary habits and the potential promotion of excessive weight gain. The objective of the current study was to determine the association between preschool fruit juice consumption and the following outcomes during childhood and adolescence: whole and total fruit intake, diet quality, likelihood of meeting current dietary recommendations, and BMI change. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 33 publications
2
8
0
1
Order By: Relevance
“…A French study found that FJ consumers tended to eat more whole fruits and vegetables than non-consumers and had significantly greater intake of fibre (18.6 g (SEM 0.2) vs. 19.8 g (SEM 0.3) (p value < 0.0001)) [59]. This and other studies [54] suggest that FJ is not replacing whole fruit or vegetables in the diet or being a marker of low fibre intakes; common concerns about FJ consumption.…”
Section: Associations With Nutrient Adequacysupporting
confidence: 57%
See 2 more Smart Citations
“…A French study found that FJ consumers tended to eat more whole fruits and vegetables than non-consumers and had significantly greater intake of fibre (18.6 g (SEM 0.2) vs. 19.8 g (SEM 0.3) (p value < 0.0001)) [59]. This and other studies [54] suggest that FJ is not replacing whole fruit or vegetables in the diet or being a marker of low fibre intakes; common concerns about FJ consumption.…”
Section: Associations With Nutrient Adequacysupporting
confidence: 57%
“…In a prospective study of more than 500 British children, no association was found between FJ consumption and body fatness at age 5 or 7 years [53]. A second prospective study followed up 100 US children from the age of 3-6 years, finding that regular FJ consumption was not associated with changes in body mass index but did predict higher whole fruit consumption in adolescence [54]. A third prospective study followed 7301 children aged 9-16 years for two years on average [55].…”
Section: Studies In Childrenmentioning
confidence: 95%
See 1 more Smart Citation
“…The significantly lower mean BMIz at 18 months of the children who consumed fruit juice at least once per week, compared with that of children who did not consume any fruit juice at all, may possibly be explained by a generally healthier diet. This could be viewed as consistent with previous findings that have linked fruit juice consumption to whole fruit consumption [21]. Yet, in this study, there were no association between whole fruit consumption and BMIz or overweight at 18 months of age among children in the NorthPop cohort.…”
Section: Discussionsupporting
confidence: 93%
“…Fruit juice is an established source of free sugars and considered a potential risk factor of overweight [ 11 , 18 , 19 ]. However, the relationship between fruit juice consumption and body-mass index (BMI) in children is inconsistent [ 20 , 21 , 22 ]. By contrast, whole fruit is thought of as healthy [ 23 ] and consumption is recommended due to its content of nutrients and fibers [ 18 ].…”
Section: Introductionmentioning
confidence: 99%